Następstwa dorastania w rodzinie z problemem alkoholowym ojca w narracji dorosłych dzieci alkoholików - Konopelko , Justyna (Studia Edukacyjne, 2024)
A child growing up in an alcoholic family experiences the consequences of having an addicted parent throughout childhood, adolescence, and adulthood. The article explores how individuals who grew up in families affected by a father’s alcohol addiction perceive the long-term consequences of this experience in their adult lives. The article presents an analysis of qualitative research conducted using a multiple case study method based on in-depth interviews. The interpretation of the results indicates a wide range of experiences in adulthood that, according to the respondents, stem from growing up in a family with an alcoholic father. Four categories of consequences as described by the participants were identified: internal (intrapersonal) consequences, consequences for relationships (interpersonal), self-expectations, and one’s unique life decisions.